Детская литература и вопросы мастерства: сборник статей / Дом детской книги Детгиза (Детгиз, 1956)
Экземпляры: КХ (20160627) / Инвентарный номер: 231635 / Цена: 5.40 / Сис.шифр: 8Ю / Авт.знак: Д 38 / ГРНТИ: 17 / ББК: 83